Viewpoint: Aligning vision and reality in publicly funded agricultural research for development: A case study of CGIAR - Thornton, Philip K.; Dijkman, Jeroen; Herrero, Mario; Szilagyi, Lili; Cramer, Laura K. (Elsevier, 2022)
Global food systems are currently facing unprecedented challenges with respect to production and nutritional targets, inclusivity and environmental footprint. Several recent reports highlight the need for major, rapid reconfiguration of our food systems as a result. International publicly funded agricultural research for development will play an increasingly vital role in support of such goals as reducing poverty, improving food and nutrition security, and improving natural resources and ecosystem services. Here we take stock of the work over the last decade of CGIAR, one of the major players in the agricultural research for development arena, from the perspective of published, peer-reviewed science. We do this with respect to several elements of its vision as set out in 2011, elements that are shared by many other organisations that are also working towards achieving the Sustainable Development Goals. Overall, we found a strong association between number of CGIAR publications and countries with large numbers of rural poor and high child stunting prevalence. At the same time several countries were identified that are anomalous, being either relatively over- or under-represented in the peer-reviewed literature in relation to numbers of rural poor and stunting prevalence. On average, 30% of the calories consumed in national food baskets come from food sources that are not currently the commodity focus of CGIAR research, such as fruit and vegetables. We identify possible ways in which the alignment between the strategic objectives of an agricultural research for development organisation such as CGIAR and its publicly funded science outputs might be further strengthened, for maximum impact in the nine years that are left for the world to achieve the Sustainable Development Goals.